Distribution and Identification of Pepper yellow leaf curl Indonesia virus Infecting Chili Pepper in Bali Island - Selangga, Dewa Gede Wiryangga; Wiyono, Suryo; Susila, Anas Dinurrohman; Hidayat, Sri Hendrastuti (Jurnal Fitopatologi Indonesia, 2022)
Yellow leaf curl disease in chili pepper has been reported in Bali Island since the early 2012. Research was conducted to identify the virus causing this disease and disease distribution in Bali. Field survey was carried out to observe disease intensity and to collect field samples from several chili pepper growing areas in Bali (Karangasem, Bangli, Tabanan, and Gianyar). Begomovirus identification from field samples was then conducted by polymerase chain reaction method using universal primers SPG1/SPG2, followed by an analysis of the amplified target DNA sequences. The incidence of pepper yellow leaf curl disease reached 100% at all sites and disease severity reached 18%−87%. Begomovirus specific DNA fragment measuring 912 bp was successfully amplified from 12 field samples. Sequence analysis of DNA fragments showed the highest homology with Pepper yellow leaf curl Indonesia virus (PYLCIV). Further phylogenetic analysis confirmed the relationship between PYLCIV isolates from Bali and various PYLCIV isolates from Indonesia.